Multivariant Disease Detection from Different Plant Leaves and Classification using Multiclass Support Vector Machine (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organic farming is becoming smarter. Unfavourable conditions, such as drought or lack of nutrients, or excessive water, will negatively affect crop production. We will grow a good crop if we have a sensor that watches over the garden. A solution is being implemented by computer-aided image processing in short, we'da first approximation, our best approach is to treat the disturbance in the leaf is to make sophisticated machinery that picks up on it. In the current issue of "Science and Cooking", find the disease in tomato, potato, grape, apple and corn plant leaves. Plant germination is usually affecting early blight, Bacterial spot, leaf mould, common rust etc. Manually monitoring plant diseases is quite tough. It necessitates a great deal of effort, knowledge of plant diseases, and an inordinate length of processing time. As a result, image processing is utilized to detect plant illnesses.  Image acquisition, image processing, and image analysis are all processes in the disease detection process. image segmentation, feature extraction, pre-processing and in addition, Multi class support vector machine classifiers (MCSVMs) are used in this work.